Food Demand Meta-Elasticities (FDME) Database - International Food Policy Research Institute (International Food Policy Research Institute, 2025)
The Food Demand Meta-Elasticities (FDME) database is a combination of three inter-related datasets of food demand elasticities. All three datasets are based on the results of a comprehensive global systematic literature review and meta-analysis of income and price elasticities compiling over 13,000 elasticity estimates from 215 peer-reviewed studies published between 1974 and 2022. The final meta-sample covers 57 countries and includes 6,572 income elasticity estimates and 6,701 price elasticity estimates.